Cases in finance - DeMello, Jim (McGraw-Hill/Irwin, 2006)
This is a book of hypothetical cases written to give students real examples of key finance concepts. Each case contains a strong critical thinking/analytical component. The cases match topics covered by all of our undergraduate books, making it the perfect companion. Each case is 3-4 pages in length, and concludes with questions and problems that walk students through calculations and critical analysis of the case to help them make business decisions.